(untitled) (Research, Society and Development, 2021)
The evoked potential of long latency Mismatch Negativity (MMN) refers objectively as an electrophysiological method to the abilities of sound discrimination, auditory processing, auditory memory and involuntary attention at central level. Such skills are found differently between musicians and non-musicians and MMN is used in an objective way to detect them. Objective: to carry out a systematic review to check if there are differences in latency and amplitude presented by MMN in musicians and non-musicians. Method: The research was carried out between September and November 2020, in the electronic databases Pubmed, ScienceDirect, BVS (Lilacs), Scopus, Circumpolar Health Bibliographic Database, SciELO, Embase, Web of science and Cochrane Central Register of Controlled Trials (CENTRAL), as well as the gray literature bases OpenGrey.eu, DissOnline, The New York Academy of Medicine, Clinical Evidence and Clinical Trials, using the descriptors as follows Music OR musician OR musicians AND potential mismatch negavitity OR MMN OR evoked potentials auditory OR Long Latency . Results: 9 articles were found, of which 7 addressed that musicians outperformed non-musicians in their latencies and amplitudes of MMN, in contrast 2 articles did not differentiate the latencies and amplitudes between musicians and non-musicians. Conclusion: In a large majority of studies, musicians showed a superiority to non-musicians in amplitude, which means that the neural abilities of auditory and behavioral discrimination of musicians surpass those of non-musicians, musicians presented lower latency of MMN, even exceeding not musicians.